Relationship Between Age With Peripheral White Blood Cell Count in Septic Patients in Two Hospitals in Tehran - Zohre Aminzade; Elham Parsa (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: In the elderly, total WBc decreases slightly. in response to sepsis the increase in WBc is so dramatic. There are some reports about effects of increasing the number of WBc as a predisposing factor of bacteremia and further association of neutrophili a and leukopenia with increased mortality rate in the elderly. The aim of this study was to determine relationship between age and peripheral WBc counts in young versus elderly patients with sepsis. Methods & Materials: A case-control study was designed on 65 admitted septic patients over 65 years of age as cases and 65 admitted septic patients less than65 years of age as controls according to Loghman Hakim and Booali Hospitals, during 2001- 2006. Results: Mean WBc was 17061/54±1424/2 in the cases and 13567/7±9888 in the controls. There was not a significant difference between mean of WBe. There was a significant difference between mean of pulse rate, and oral temperature in two groups. (P<0.05). In elderly, there was a significant correlation between age with history of infection and age with history of hospitalization during last month and also a significant correlation between age with source of probable infection ((P<0.05), but there was no a significant correlation between death with WBc and death with source of probable infection. Conclusion: Bacteremia in elderly can be afebrile and with pulse rate less than otber patients. The history of infection and history of hospitalization during last month in elderly with sepsis are considered to be important in evaluation.